FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT STRES PADA ANAK USIA SEKOLAH DASAR YANG SIBUK DAN TIDAK SIBUK - Pranadji, Diah Krisnatuti; Nurlaela, Nurlaela (Jurnal Ilmu Keluarga dan Konsumen, 2009)
The purpose of this study was to examine factors that influenced stress degree in busy and unbusy children of elementary school. The research conducted in SD Bina Insani Bogor. The research method was cross sectional study with 30 samples of busy children and 30 samples of unbusy children. The site of the research was selected purposively by considering that SD Bina Insani Bogor is one of the favorite private schools in Bogor. Moreover, SD Bina Insani Bogor has tight schedule and also has a large numbers of students who participated in extracurricular activities/activities after school program. The results showed that there were significant differentiation between busy children and unbusy children in time allocation and amount of extracurricular activities/activities after school program. Female students allocated more time I extracurricular activities after school than male students. Amount of extracurricular activities/activities after school, its time allocation, and time allocation for watching TV were factors that affected stress level of the children. Finally, factors affected the degree of stress of students were the amount of extracurricular activities after school, and the time allocation for watching TV.